CircRNA-Associated CeRNAs Regulatory Axes in Retinoblastoma: A Systematic Scoping Review - Asadi, Mohammad Reza; Moslehian, Marziyeh Sadat; Sabaie, Hani; Sharifi-Bonab, Mirmohsen; Hakimi, Parvin; Hussen, Bashdar Mahmud; Taheri, Mohammad; Rakhshan, Azadeh; Rezazadeh, Maryam (Frontiers in Oncology, 2022)
Retinoblastoma (RB) is one of the most common childhood cancers caused by RB gene mutations (tumor suppressor gene in various patients). A better understanding of molecular pathways and the development of new diagnostic approaches may lead to better treatment for RB patients. The number of studies on ceRNA axes is increasing, emphasizing the significance of these axes in RB. Circular RNAs (circRNAs) play a vital role in competing endogenous RNA (ceRNA) regulatory axes by sponging microRNAs and regulating gene expression. Because of the broadness of ceRNA interaction networks, they may assist in investigating treatment targets in RB. This study conducted a systematic scoping review to evaluate verified loops of ceRNA in RB, focusing on the ceRNA axis and its relationship to circRNAs. This scoping review was carried out using a six-step strategy and the Prisma guideline, and it involved systematically searching the publications of seven databases. Out of 363 records, sixteen articles were entirely consistent with the defined inclusion criteria and were summarized in the relevant table. The majority of the studies focused on the circRNAs circ_0000527, circ_0000034, and circTET1, with approximately two-fifths of the studies focusing on a single circRNA. Understanding the many features of this regulatory structure may help elucidate RB’s unknown causative factors and provide novel molecular potential therapeutic targets and medical fields.